FISCAL AND TAX IMPLICATIONS OF AN INCREASE IN CROSS-BORDER LABOUR - Loso Judijanto (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Increased cross-border labour mobility is a global phenomenon that has a significant impact on fiscal and taxation policies, both in the country of origin and the country of destination. This study aims to analyse the fiscal and tax implications of this phenomenon using a literature review method of various related literature, regulations, and empirical data. The results show that remittances from migrant workers are an important source of foreign exchange that contributes to the economic growth and fiscal stability of the home country. However, there are challenges in optimising tax revenue due to differences in taxation systems, the risk of double taxation, and limited education and tax compliance of migrant workers. On the other hand, destination countries benefit from the tax contribution of foreign workers, but are also faced with issues of social protection and regulatory harmonisation. Therefore, an integrated policy is needed that includes harmonisation of international tax treaties, improvement of worker education and protection, and strengthening of monitoring systems to ensure optimal benefits and fiscal justice from cross-border labour mobility.